At the Roots of the Tree of Life: Marija Gimbutas among the Family Women - Vaitkevičienė , Daiva (Tautosakos darbai, 2021)
The intellectual legacy of Marija Gimbutas – scholar, theoretician and practical archeologist, an active, versatile and sensitive personality – has been hitherto little investigated, including in particular her Lithuanian studies. The article focuses on the relationship that Marija Gimbutas had with her family, especially highlighting her connection with her mother – Veronika Janulaitytė-Alseikienė. Gimbutas’ mother Veronika Janulaitytė-Alseikienė (1883–1971) was among the very few Lithuanian women of the peasant descent that managed to obtain the university education at the turn of the 19th – 20th centuries. In 1908, she defended her doctoral thesis in medicine in Berlin. However, due to various circumstances, including nostalgia for her homeland, she discontinued her scholarly work in Germany, returning to the Russian Empire of that time. After the WWI, together with her husband Danielius Alseika (doctor, politician and editor of numerous Lithuanian publications) Veronika established the first Lithuanian hospital in Vilnius, engaging in the medical, social and educational activities. Marija Gimbutas’ parents were a rather different personalities. Her father was an idealist ardently pursuing his social and political ideas, while her mother was a rational and practical woman, who took care of maintaining the hospital, social welfare and family matters. Since early childhood, Marija’s mother enfolded her daughter with her care, attempting to provide her with everything that she considered valuable, and devoting special attention to her education. Gimbutas’ cousin, professor Meilė Lukšienė has described her mother as a “silent soul”, since she could not fully realize her talents, but devoted all her energy to enable her daughter to do so. It is obvious that Marija inherited most of her character features from her mother, including courage, determination, inexhaustible energy, industriousness, and vitality. In spite of the passionate care that she received from her mother, in her childhood and youth Marija regarded her father as her personal ideal and as an example to follow. She considered her rational and pragmatic mother as a given, as someone providing her with good living conditions, and directed her admiration and love to her father. She felt inspired by Danielius Alseika’s ideals, his broad humanitarian worldview, his articles on the Lithuanian culture and his devoted work as editor and publisher of the Lithuanian books. She regarded her father as an embodiment of human creativity. However, he died when Marija was just fifteen years old. It took her considerable time afterwards to fully appreciate her mother’s love, her dedicated care of the children, and her hard work to ensure family’s welfare and security. The author of the article assumes that the active, vital and creative energy, which Marija saw embodied in her father’s image and political activities, subsequently inspired her impressive theory of the Indo-Europeans spreading across the whole of Europe. And only later, her down-to-earth side of life became more visible, manifesting in her theory of matristic culture of the ancient Europe. Marija Gimbutas fully and consciously appreciated her connection with her mother only after she got married and had her daughter Danutė born in 1943. Unfortunately, the development of this connection was suspended because of the necessity for her to flee from Lithuania, which was occupied by the Soviet troops in 1944. Further on, Marija’s connection with her mother and other female members of her family (her aunt Julija Matjošaitienė and her cousin Meilė Matjošaitytė-Lukšienė) was maintained from emigration. The first letter from Marija reached Lithuania only after seven years following her departure, and regular correspondence could be established only after Stalin’s death. However, when acquiring this possibility, Marija corresponded very actively: she has written over 400 letters and over 200 postcards to her mother. Another way of maintaining connection with her family was sending packages. Ample gifts were shipped from America to Lithuania; however, Marija received equally dear presents from Lithuania in return. Veronika Alseikienė saw sending gifts as an expression of her love to her daughter, as means of creating the Lithuanian atmosphere in Marija’s home and supporting her Lithuanian cultural activities in America. For Marija, things that she received were primarily means of connection with her mother. Only in the summer of 1960, there finally was hope of meeting in person. Although possibilities of visiting the Soviet Union from the USA were severely restricted, Marija Gimbutas managed to visit her mother at least seven times. These short encounters allowed her to establish a closer connection, and during long times of separation to envision her mother’s home in Kaunas. Anyway, Marija Gimbutas had a special talent of feeling her loved ones in spite of the distance that separated them. She has described her extraordinary state of mind and her telepathic ability of seeing and feeling her mother, who was hospitalized after a surgery at that time. She experienced a deep feeling of connection also on the day of her mother’s funeral, having a vision of her mother finally being able to visit her daughter’s home in Topanga – at least after her death. For Gimbutas, considerations of life and death were not merely academic studies of the ancient European religion, but constituted an inherent part of her personality. She discussed the indestructible nature of the vital energy, and the human ability to feel close proximity with the deceased, who never left us completely. The religious images and phenomena that she examined were her reality. In her letters to her mother, Gimbutas repeatedly used words like life, living, enliven, strength, vigor, indicating that she gained strength and energy from this connection. In one case, she even described the tree of life when discussing folk art ornaments on an item that she had received from her mother. The women that surrounded Marija Gimbutas from her early childhood, the connection with her mother that she maintained even in emigration, the female solidarity and spiritual community that she had with her aunt Julija Matjošaitienė and her cousin Meilė Lukšienė constituted sources of vital energy for Marija Gimbutas that supported not only herself, but also her theory of the goddesses’ civilization. The example and authority of her mother and other female relatives enabled Marija to see and recognize in her archeological findings the active and creative female side, creating prerequisites of looking for the female goddesses in the global archeological Paleolithic and Neolithic cultures. Marija Gimbutas could have hardly developed enough courage to establish women as creators of the European civilization, were it not for the strong, brave and active women that surrounded her form her childhood and presented powerful examples for her to follow.